2022
DOI: 10.1038/s41398-022-02128-0
|View full text |Cite
|
Sign up to set email alerts
|

Layer III pyramidal cells in the prefrontal cortex reveal morphological changes in subjects with depression, schizophrenia, and suicide

Abstract: Brodmann Area 46 (BA46) has long been regarded as a hotspot of disease pathology in individuals with schizophrenia (SCH) and major depressive disorder (MDD). Pyramidal neurons in layer III of the Brodmann Area 46 (BA46) project to other cortical regions and play a fundamental role in corticocortical and thalamocortical circuits. The AutoCUTS-LM pipeline was used to study the 3-dimensional structural morphology and spatial organization of pyramidal cells. Using quantitative light microscopy, we used stereology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…Our finding of a smaller (−8.7%) mean size of DLPFC L3PNs in schizophrenia replicates prior reports using Nissl staining (−9.2%) ( Pierri et al, 2001 ) or Golgi labeling (−9.1%) ( Glantz and Lewis, 2000 ) in other cohorts of schizophrenia subjects, and are consistent with other studies reporting smaller sizes of L3PNs in in the illness ( Pierri et al, 2001 ; Rajkowska et al, 1998 ; Glantz and Lewis, 2000 ; Sweet et al, 2003 ; Sweet et al, 2004 ; Larsen et al, 2022 ). Previous findings suggest that smaller L3PNs in schizophrenia have fewer dendritic spines ( Glantz and Lewis, 2000 ; Garey et al, 1998 ; Konopaske et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a smaller (−8.7%) mean size of DLPFC L3PNs in schizophrenia replicates prior reports using Nissl staining (−9.2%) ( Pierri et al, 2001 ) or Golgi labeling (−9.1%) ( Glantz and Lewis, 2000 ) in other cohorts of schizophrenia subjects, and are consistent with other studies reporting smaller sizes of L3PNs in in the illness ( Pierri et al, 2001 ; Rajkowska et al, 1998 ; Glantz and Lewis, 2000 ; Sweet et al, 2003 ; Sweet et al, 2004 ; Larsen et al, 2022 ). Previous findings suggest that smaller L3PNs in schizophrenia have fewer dendritic spines ( Glantz and Lewis, 2000 ; Garey et al, 1998 ; Konopaske et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous postmortem studies have also observed that changes in the morphological features of subiculum neurons were also similar yet more pronounced in schizophrenia patients compared to patients with mood disorders [69]. Another study, measured the Layer III pyramidal cells in the prefrontal cortex using postmortem tissue similarly revealed changes in the morphology of patients with major depression, and the changes were more exacerbated in neurons from schizophrenia patients [70]. This strengthens our results that neurons derived from patients with mood disorders (the co-twins) exhibit morphological and synaptic alterations that are stronger in patients with schizophrenia (the affected twins).…”
Section: Discussionmentioning
confidence: 79%
“…In the context of SZ, decreased number of neurons has been identified in the layer three of DLPFC (van Berlekom et al, 2020). Besides, a study in the BA46 in DLPFC found morphological alterations in the pyramidal cells, however, the authors did not find an alteration in the spatial organization of pyramidal cells, suggesting a normal neuronal migration in SZ subjects (Larsen et al, 2022)In agreement with our study, CYFIP2 has also been found downregulated in a proteomic study in the cingulate anterior (Föcking et al, 2015). However, the relation between CYFIP2 negative symptoms has not been studied in SZ.…”
Section: Altered Expression Of Cyfip2 In Szmentioning
confidence: 94%